CTIM-21. PEPTIDE VACCINE DIRECTED TO CMV pp65 FOR TREATMENT OF RECURRENT MALIGNANT GLIOMA AND MEDULLOBLASTOMA IN CHILDREN AND YOUNG ADULTS: PRELIMINARY RESULTS OF A PHASE I TRIAL. (9th November 2020) - Thompson, Eric; Landi, Daniel; Thompson, Eric; Lipp, Eric; Balajonda, Bea; Herndon, James; Buckley, Evan; Flahiff, Charlene; Jaggers, Denise; Schroeder, Kristin; Randazzo, Dina; Desjardins, Annick; et al.
Abstract: INTRODUCTION: The cytomegalovirus (CMV) antigen, pp65, is ubiquitously expressed in malignant glioma and medulloblastoma but not in healthy brain. The objective of this Phase I trial (NCT03299309) was to assess the safety and feasibility of a novel pp65 peptide vaccine (PEP-CMV) in children and young adults with recurrent medulloblastoma and malignant glioma. METHODS: Vaccines contain a synthetic long peptide (SLP) of 26 amino acids encoding multiple potential class I, class II, and antibody epitopes of CMV pp65 across several haplotypes. This SLP is administered as an emulsion in Montanide ISA 51. Patients receive a single course of temozolomide to induce lymphopenia, tetanus/diphtheria toxoid site preconditioning, then vaccines administered intradermally every two weeks for 3 doses, then monthly. RESULTS: To date, 17 patients have been enrolled. Diagnoses include medulloblastoma (n=1), glioblastoma (n=9), anaplastic oligodendroglioma (n=2), anaplastic astrocytoma (n=2), and malignant glioma NOS (n=3). Mean number of prior treatment regimens is 4.9 (range 1–12). Mean age is 22yo (range 6–35) and 41% of patients are male. The median KPS is 80. The median number of vaccines given at time of analysis is 3.3 (range 1–12). There have been no ≥ 3 Grade toxicities related to the vaccine. One patient developed nausea, vomiting, palpitations, and tachycardia after vaccination and had elevated inflammatory cytokines consistent with cytokine release syndrome. Median PFS is 2.5 months (95% CI: 0.8, not estimable) and median OS is 6.5 months (95% CI 1.8, not estimable). Interim analysis of immune monitoring bloodwork and perfusion MRI to quantify responses to PEP-CMV has been delayed due to COVID-19. However, adults with GBM who received PEP-CMV (NCT02864368) had significant (p≤0.05) increases in GCSF, GM-CSF, IFN-γ, IL-10, IL-2, IL-8, MIP1-α, and TNF-α levels. CONCLUSIONS: Preliminary results demonstrate that PEP-CMV is feasible and well-tolerated in heavily pretreated, multiply recurrent patients.